PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS ANDROID PADA MATA PELAJARAN INFORMATIKA KELAS VIII DI UPT SMPN 1 MAKALE SELATAN - Gojang, Rifka; Anna Pertiwi; I Ketut Linggih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted at UPT SMPN 1 Makale Selatan and was motivated by the limited availability of digital teaching materials and printed books in the Informatics subject for Grade VIII, particularly on the Computer System topic. Although students have been permitted to use Android devices in the learning process, their utilization has not been optimal and is still limited to searching for additional information. The objectives of this study are: (1) to identify the needs for developing Android-based digital teaching materials, (2) to design Android-based digital teaching materials, and (3) to test the validity and practicality of Android-based digital teaching materials in the Informatics subject for Grade VIII. The type of research used is Research and Development (R&D) with the Richey & Klein development model, which consists of three stages: Planning, Production, and Evaluation. The research subjects included media experts, material experts, teachers, and 29 students of Grade VIII A. The instruments used in this study were observation, interviews, and questionnaires for validity and practicality testing. The results showed that the Android-based digital teaching materials developed obtained a validity score of 91.25% from media experts (very valid) and 90% from material experts (very valid). The practicality test results reached 88.06% from students (very practical) and 87.5% from the teacher (very practical). Thus, it can be concluded that the Android-based digital teaching materials developed using the Kodular platform are valid, practical, and feasible to be used in teaching Informatics for Grade VIII at UPT SMPN 1 Makale Selatan.